Variability in the breeding season of Black Swans Cygnus atratus in southeast Queensland, Australia - Coleman, Lucy A.; Coleman, Jonathan T. (Wildfowl, 2024)
Variability in the duration of the breeding season and the mean number of annual breeding attempts recorded for Black Swans Cygnus atratus in southeast Queensland, Australia, were evaluated in relation to environmental variables. There was a significant correlation between the extent of the breeding season (measured as the number of months in which eggs were hatched) with both the number of breeding attempts made by paired birds in that year and also the number of territorial pairs recorded. This may reflect changes in the timing of breeding by individual pairs to reduce competition for favoured breeding and foraging locations. The number of breeding attempts per territorial pair in any one year was influenced primarily by summer rainfall and the Southern Oscillation Index (SOI), with higher values for both of these environmental variables being associated with more breeding attempts and increasing numbers of breeding pairs. We therefore suggest that the increasing numbers of breeding pairs, and also the increasing numbers of breeding attempts associated with more favourable weather conditions, may have led to the longer breeding seasons recorded for Black Swans in southeast Queensland in recent years.